Thyroid Hemiagenesis Associated with Hashimoto’s Thyroiditis - D. Nsame; A. Chadli; L. Hallab; S. El Aziz; H. El Ghomari; A. Farouqi (Case Reports in Endocrinology)
Thyroid hemiagenesis is a rare congenital anomaly resulting from failure of one thyroid lobe development. We report a 23-year-old female presented with Hashimoto’s thyroiditis in left lobe, associated with hemiagenesis of right lobe and isthmus which was previously diagnosed as Graves’ hyperthyroidism, but developed further into Hashimoto’s thyroiditis after being treated with antithyroid drugs. The symptoms of hyperthyroidism in the current case led to the diagnostic confirmation by scintiscanning of an absent lobe. The antithyroid pharmacotherapy by thiamazole was used. However, due to symptoms of hypothyroidism, it was discontinued two months later, so thyroid hormone substitution was reintroduced. Antithyroid antibody studies and ultrasonography documented the presence of Hashimoto’s thyroiditis.